Aqueous Dual‐Ion Batteries: Enabling Natural Graphite in High‐Voltage Aqueous Graphite || Zn Metal Dual‐Ion Batteries (Adv. Energy Mater. 41/2020). Issue 41 (3rd November 2020) - Rodríguez‐Pérez, Ismael A.; Zhang, Lu; Wrogemann, Jens Matthies; Driscoll, Darren M.; Sushko, Maria L.; Han, Kee Sung; Fulton, John L.; Engelhard, Mark H.; Balasubramanian, Mahalingam; Viswanathan, Vilayanur V.; Murugesan, Vijayakumar; Li, Xiaolin; et al.
Abstract : In article number 2001256 Ismael A. Rodríguez‐Pérez, Tobias Placke and co‐workers show that graphite, a redox amphoteric material can reversibly store anions electrochemically in an aqueous battery using a water‐in‐bisalt electrolyte and a zinc metal anode. The graphite forms a stage‐3 graphite intercalation compound that stores anions at high potentials. The battery is intrinsically safe, providing performance that may enable the development of aqueous dual‐ion batteries for grid‐level applications. Image credit: Hongkyung Lee.